The 4th International Whale Shark Conference 2016
DOI: 10.5339/qproc.2016.iwsc4.16
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the South Ari atoll whale shark, Rhincodon typus, aggregation

Abstract: Background Examples of aggregations of large Chondrichthyes are well known worldwide and occur mostly in response to seasonal increases in prey abundance. In the Maldives, whale sharks, Rhincodon typus, are thought to have a semi-annual residency pattern, moving west from December to April and east from May to November. However, an important aggregation of predominantly immature male whale sharks seems to be persistent all year round throughout the South Ari atoll region. Understanding residency patterns of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…For whale shark, coastal areas of shallow bathymetry in close proximity to the reef slope and deeper water were preferred habitats and whales were common found in this area (De la Parra Venegas et al 2011, Donati et al 2016, Diamant et al 2016). This whale behavior is in accordance with the stranding case of pilot whale in this study where the whale aggregations were found in shallow water.…”
Section: Resultsmentioning
confidence: 99%
“…For whale shark, coastal areas of shallow bathymetry in close proximity to the reef slope and deeper water were preferred habitats and whales were common found in this area (De la Parra Venegas et al 2011, Donati et al 2016, Diamant et al 2016). This whale behavior is in accordance with the stranding case of pilot whale in this study where the whale aggregations were found in shallow water.…”
Section: Resultsmentioning
confidence: 99%
“…spawn in Belize ( Heyman et al, 2001 ). However, Donati et al (2016) describe the aggregation at South Ari atoll as a yearlong phenomenon with no seasonal peak and there is a current lack of understanding as to the main cause of this aggregation if it is not seasonally prey driven. Nonetheless, these whale sharks will feed on plankton and various spawn in the shallow coastal waters where they are regularly observed ( Hoffmayer et al, 2007 ; Motta et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown almost all R. typus aggregations occur in coastal areas of shallow bathymetry in close proximity to the reef slope and deeper water ( De la Parra Venegas et al, 2011 ; Donati et al, 2016 ; Diamant et al, 2016 ). Past studies have illustrated increased zooplankton availability in areas of steep bathymetry, which R. typus preys upon ( Bouchet et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the coastal waters of the Republic of Maldives, whale sharks are seasonally present and show a semi-annual residency pattern. They move along the western atolls during the northeast monsoon (from December to April), and along the eastern atolls during the southwest monsoon (from May to November) (Anderson & Ahmed 1993;Riley et al 2010;Anderson et al 2011;Cagua et al 2014;Donati et al 2016). Movements of whale sharks along the double chains of atolls of the Maldives, appear to be affected principally by the seasonal variability in productivity (Anderson et al 2011) and by ocean currents (Anderson & Ahmed 1993;Wilson et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The south region of Ari Atoll (Alif Dhaalu Atoll) represents an exception compared to the other atolls in the Maldives. Indeed, although the driver of aggregation has not to be defined yet, this area hosts year-long aggregations, mainly composed of juvenile males (Riley et al 2010;Donati et al 2016;Perry et al 2018;Allen et al 2021;Harvey-Carroll et al 2021). The high re-sighting rate of some individuals suggests a high site fidelity over the years, and the absence of adult, neonates, and female indicates that this area might be a "secondary nursery area" and a developmental habitat for juvenile males (Perry et al 2018;Allen et al 2021;Harvey-Carroll et al 2021).…”
Section: Introductionmentioning
confidence: 99%